13+3x-9=10x-14-5x

Simple and best practice solution for 13+3x-9=10x-14-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13+3x-9=10x-14-5x equation:


Simplifying
13 + 3x + -9 = 10x + -14 + -5x

Reorder the terms:
13 + -9 + 3x = 10x + -14 + -5x

Combine like terms: 13 + -9 = 4
4 + 3x = 10x + -14 + -5x

Reorder the terms:
4 + 3x = -14 + 10x + -5x

Combine like terms: 10x + -5x = 5x
4 + 3x = -14 + 5x

Solving
4 + 3x = -14 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
4 + 3x + -5x = -14 + 5x + -5x

Combine like terms: 3x + -5x = -2x
4 + -2x = -14 + 5x + -5x

Combine like terms: 5x + -5x = 0
4 + -2x = -14 + 0
4 + -2x = -14

Add '-4' to each side of the equation.
4 + -4 + -2x = -14 + -4

Combine like terms: 4 + -4 = 0
0 + -2x = -14 + -4
-2x = -14 + -4

Combine like terms: -14 + -4 = -18
-2x = -18

Divide each side by '-2'.
x = 9

Simplifying
x = 9

See similar equations:

| -9=108 | | 3x^2-3=45 | | x^2-24x+1=0 | | 100(x-3)=450-50 | | t/3-2=9 | | -6(8+6k)=-228 | | 7/5(40) | | x+7/5x=96 | | 6d/4=24 | | -153-12x=71+2x | | -5+7=5x-4(x-1) | | 9Y-1=y-5 | | D(3-7)-12=0 | | 6m/7-3=9 | | -82-3x=11x+170 | | 7m-10m=27 | | .5=.09 | | 9(w-4)=7w-44 | | 3+573g=3g | | 3+573=3g | | 3m^3-32m-8=0 | | 3+573=g | | 3a+3a=16+18a | | an=-7+6 | | -98-3x=98-10x | | .66t+4=2 | | 4096=r^6 | | 2x+5y=-34 | | t=96t-16t^2 | | l=5+2x | | 4-6w=3*1/2+w/2 | | 48-x=4*x-7 |

Equations solver categories